Comparative economic analysis of support policies for solar PV in the most representative EU countries. (February 2015) - Dusonchet, L.; Telaretti, E.
Abstract: The purpose of this paper is to study the positions of some European Union (EU) countries on the development of PV systems. After a review of the main support policies for PV systems in Europe, the specific situations of five representative countries (France, Germany, Greece, Italy and the U.K.) are examined, with the purpose of describing the main differences in their implementation of support policies adopted for PV systems. In particular, comparisons based on economic indexes such as the net present value (NPV) and the internal rate of return (IRR) are carried out for different sized PV systems, showing that in some situations support policies can be inconvenient for the PV system owner. The paper also shows that the best profitability for a PV system owner is obtained in those countries in which there is an active electricity compensation scheme. The comparative analysis carried out in this work could help: – to assess the impact of PV energy policies in European member states; – to predict how the PV market could evolve in the selected EU member states; – to gain an insight into the future of possible energy policies.